Nilai, Sikap Dan Kepuasan Kerja Dalam Perilaku Organisasi Pendidikan - Ade Saputra; Kasful Anwar; Jamrizal Jamrizal (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
In building organizational behavior, we must pay attention to individual aspects in terms of values, attitudes and organizational job satisfaction. According to McShane & Von Glinow (2010) Values ​​are interpreted as a reflection of a person's personality in guiding various provisions or decisions and actions in accordance with the work of the organization. Attitudes are basically evaluative statements, either favorable or unfavorable regarding objects, people or events. Attitude reflects how someone feels about something. A gentle attitude is a very important attitude and must be possessed, especially for a leader, to gain sympathy from the people he leads. Meanwhile, according to Mangkunegara (2005), job satisfaction can be measured by: How a leader places his subordinates in jobs that suit their talents and interests; The implementation of quality supervision, financial guarantees, opportunities for promotion, social interactions and working relationships within teams also influence a person's job satisfaction.